Transitional justice in Tunisia: a critical assessment of the External Actors’ Involvement - Jmal, Nadia (Frontiers in Political Science, 2025)
Despite the initial consensus and optimism surrounding the Tunisian government’s push for transitional justice (TJ) in early 2012, and the enthusiasm of major donors and international organizations to support it, the process faced major challenges. Following the 2011 revolution, Tunisia’s civil society scene was soon saturated with a wide range of international actors, including INGOs, UN entities, and donors, promoting a standardized and holistic approach that often overlooked the limited capacity of the newly established transitional justice institutions. Very soon, the recommended technical and top-down interventions revealed their downsides, especially since the TJ process faced significant political hostility starting in 2014, coinciding with the rise of Nidaa Tounes, a political party that united old regime figures and had little interest in ensuring accountability. The transitional justice mechanisms, most notably the Truth and Dignity Commission (TDC) and the Specialized Criminal Chambers (SCC), often lacked the procedural flexibility and resources needed to withstand political pressures. Despite publicized efforts by domestic and international actors, many Tunisians, including victims, remained dissatisfied with the pace and substance of the transitional justice process. The report argues that a critical assessment of international actors’ role is essential to ensure that future interventions are context-sensitive, politically informed and responsive to the needs of affected communities.